An ultra-high sensitive plasmonic refractive index sensor using an elliptical resonator and MIM waveguide - Khani, Shiva; Hayati, Mohsen (Superlattices and microstructures, 2021)
In this paper, an elliptical resonator coupled to a straight metal-insulator-metal waveguide through a silicon layer is used for sensing application. The finite-difference time-domain method is used for the numerical investigation of the proposed structure. Such a structure demonstrates a multi resonance mode in the transmission spectrum. Based on the obtained results, the sensitivity can be reached to a value as high as 550 nm per refractive-index unit with a high FOM value of 282.5 RIU−1 around the resonance wavelength of 592 nm. In this structure, in addition to using a high Q-factor resonator, the resonance profile is localized and concentrated on the analyte to achieve an ultra-high sensitive refractive index sensor. Also, the effect of structural parameters on the transmission spectrum is investigated by sweeping them. Taking into account the obtained notable specifications such as ultra-high sensitivity and simplicity of the design and fabrication process, the presented structure can be employed in optical integrated circuits, particularly in high sensitivity sensors. •A novel plasmonic structure for detection of refractive index is proposed.•The designed topology is based on an elliptical resonator coupled to a straight MIM waveguide through a silicon layer.•A high FOM value of 282.5, a high sensitivity value of 550 nm/RIU, and a small FWHM value of 1.947 nm are obtained.•In addition to using a high-Q factor resonator, the resonance profile is localized on the analyte to achieve a high FOM.•The proposed structure benefits from simplicity in the design and fabrication process.